Advances on Broadband and Wireless Computing, Communication and Applications Proceedings of the 13th International Conference on Broadband and Wireless Computing, Communication and Applications (BWCCA-2018) - Barolli, Leonard; Leu, Fang-Yie; Enokido, Tomoya; Chen, Hsing-Chung (Lecture Notes on Data Engineering and Communications Technologies,, 2019)
This book presents on the latest research findings, and innovative research methods and development techniques related to the emerging areas of broadband and wireless computing from both theoretical and practical perspectives. Information networking is evolving rapidly with various kinds of networks with different characteristics emerging and being integrated into heterogeneous networks. As a result, a number of interconnection problems can occur at different levels of the communicating entities and communication networks' hardware and software design. These networks need to manage an increasing usage demand, provide support for a significant number of services, guarantee their QoS, and optimize the network resources. The success of all-IP networking and wireless technology has changed the way of life for people around the world, and the advances in electronic integration and wireless communications will pave the way for access to the wireless networks on the fly. This in turn means that all electronic devices will be able to exchange the information with each other in a ubiquitous way whenever necessary.